Scaling up the biogenic emissions from test sites at Castelporziano (Atmospheric Environment, 1997)
On the basis of measurements of emission rates, Leaf Area Indices (LAI) and biometric data for 17 species and 15 land-cover types, a first scaling up of biogenic emissions for the Castelporziano test site is elaborated It includes the application of different procedures for scaling up, by combining parameters (e.g. LAI, biomass, vegetation coverage, canopy layering, insolation) with emission rates and algorithms in a spatial model. This approach consists of the following steps: (i) elaboration of a pseudo-3D Geographical Information System (GIS) for the test site St. Quercio, and 2D GIS for pseudosteppe, dunes and whole Castelporziano, (ii) calculations of relations between diameter at breast height (dbh), biomass and LA1 from literature and our own data, at St. Quercio, (iii) application of an insolation model in the stands for one to two canop:y layers and surfaces in a l/4 square meter resolution, at St. Quercio; (iv) classified incoming light is driving the emissions of monoterpenes from Stone pine and Holm oak at the test site St. Quercio. For temperature we do not scale up and apply any algorithm to date, but we can show some preliminary surface temperature data from remote sensing activities, possibly to be used during further campaigns. Calculations of total emission fluxes are intercompared for the test site St. Quercio according to the different calculation rules, e.g. the relevancy of spatial effects. The differences between the biomass-based fluxes and the LAI-based fluxes are in the range of 5-30%. The application of the GIS model for light interception for the pine canopy, and for’two canopy layers for Holm oak, is shown for the open stands at St. Quercio. The resulting biogenic emissions are in good accordance with the ones calculated only via biomass or LAI, and the lower parts of a crown seem to be negligible in terms of biogenic emissions.